TREATMENT OF PAINFUL FLEXIBLE FLATFOOT IN CHILDREN AFTER FAILED CONSERVATIVE TREATMENT USING A MINIMALLY INVASIVE SURGERY TECHNIQUE: PAINFUL FLEXIBLE FLATFOOT TREATMENT IN CHILDREN - Bukva, Bojan; Majstorović, Marko; Ducic, Sinisa; Krivokapić, Branislav; Radlović, Vladimir; Djuričić, Goran; Begović, Ninoslav; Stojković, Jasna; Knežević, Tatjana; Nikolic, Dejan (Medical Research, 2024)
Introduction/Aim: Flexible flatfoot (FFF) is one of the most common skeletal deformity in the pediatric population, especially in preadolescence. This retrospective observational study evaluates the use of a calcaneal subtalar extra-articular arthrodesis (subtalar arthroereisis) with a one cannulated screw for the treatment of painful flexible flatfoot in children, after previously failed conservative treatment. Methods: Preadolescent and adolescent pediatric patients were observed in Department of Pediatric Orthopedic Surgery. The study included 28 feet of 15 children (5 girls and 10 boys) during a 6-year period, from 2016 to 2021. (average 26 months). The average age was 11.46 years (range 8-15 years). We performed the same operative technique under fluoroscopy for all patients. Radiographic parameters were taken before, after operative treatment, and after hardware removal. The following radiological parameters were measured: talo-calcanear (TC), talo-navicular (TN), talo-first metatarsal bone (T1MT) and calcanear pitch (CP) angles, in the anteroposterior and/or lateral views. Functional outcomes (extension and eversion of the foot) before surgery and after hardware removal were compared. Results: After operative treatment, midfoot radiographic parameters were not significantly altered; however, both the subtalar joint and forefoot were significantly improved: both radiologically and clinically. Range of extension and eversion of the foot were remarkably reduced without disturbing the morphological and functional aspects of the talocrural and subtalar joints. Conclusion: Extra-articular arthrodesis, using a cannulated screw in a minimally invasive technique, represents an optimal method for the operative treatment of symptomatic flexible flatfoot in children. This technique is simple, efficient and does not disrupt the anatomy of the foot.